A positive photosensitive resin composition, an interlayer insulating film, and a method for producing the same
Patent Information
- Application Number
- CN202611078777.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-20
- Publication Date
- 2026-10-30
AI Technical Summary
然而,目前尚未获得能够满足上述全部性能要求的放射线敏感性树脂组合物
[0025]此外,本申请组合物中树脂所含的含羧基的不饱和单体赋予了树脂碱可溶性,确保了组合物在碱性显影液中的良好显影性能;同时,各单体之间的协同作用使树脂在显影液中的溶解速率适中,从而在显影时间超出最适范围时仍能维持良好的图案形状,有效抑制图案剥离。由此,本申请组合物兼具高感度和优异的显影宽容度。
Smart Images

Figure CN123010331A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of photosensitive resin composition technology, and more particularly to a positive photosensitive resin composition, an interlayer insulating film, and a method for preparing the same. Background Technology
[0002] In electronic components such as thin-film transistor (TFT) liquid crystal display elements, interlayer insulating films are typically provided between layered wirings to achieve electrical insulation. Positive radiation-sensitive resin compositions are widely used as materials for forming these interlayer insulating films due to their low number of processing steps and excellent flatness.
[0003] Taking a TFT-type liquid crystal display element as an example, its manufacturing process includes forming a transparent electrode film and a liquid crystal alignment film on an interlayer insulating film. During this process, the interlayer insulating film needs to withstand high temperature conditions, resist stripping solution, and irradiation with various wavelengths of light, thus requiring sufficient heat resistance, solvent resistance, and light resistance; at the same time, since it may undergo a dry etching process, it also needs to have sufficient dry etching tolerance.
[0004] In recent years, with the development of TFT liquid crystal display elements towards larger screens, higher resolution, and thinner profiles, the performance requirements for compositions used in forming interlayer insulating films have become increasingly stringent. These requirements not only demand high sensitivity but also low dielectric constant and high light transmittance in the formed film. Furthermore, during the development process, if the development time is slightly longer than the optimal time, the developer can easily penetrate to the interface between the pattern and the substrate, leading to pattern peeling and consequently a decrease in yield.
[0005] Therefore, there is a desire to develop a composition that exhibits excellent coatability, high sensitivity to radiation, maintains good pattern shape even when development time exceeds a specified range, and produces an interlayer insulating film with excellent heat resistance, solvent resistance, light transmittance, and dry etching resistance. However, a radiation-sensitive resin composition that meets all of the above performance requirements has not yet been obtained. Summary of the Invention
[0006] The purpose of this application is to provide a positive photosensitive resin composition, an interlayer insulating film, and a method for preparing the same, in order to solve the above-mentioned problems.
[0007] To achieve the above objectives, this application adopts the following technical solution: This application provides a positive photosensitive resin composition, wherein the raw materials of the positive photosensitive resin composition include, by weight, 100 parts of alkali-soluble acrylic resin, 10-30 parts of photosensitive compound, 0.5-3 parts of silane coupling agent, 0.05-0.5 parts of leveling agent, and 30-80 parts of organic solvent.
[0008] Optionally, by weight, the raw materials of the alkali-soluble acrylic resin include: 10-15 parts methacrylic acid, 15-20 parts hydroquinone monomethacrylate, 4-22 parts methyl methacrylate, 4-8 parts silane monomer, 4-12 parts styrene, 5-10 parts dicyclopentyl methacrylate, 10-15 parts glycidyl methacrylate, 5-10 parts 3,4-epoxycyclohexylmethyl methacrylate, 15-20 parts tetrahydrofuran methacrylate, and 10-15 parts 4-acryloylmorpholine.
[0009] Optionally, the alkali-soluble acrylic resin is a homogeneous solution.
[0010] The solid content of the homogeneous solution is 30-40 wt%; The solvent for the homogeneous solution includes diethylene glycol methyl ethyl ether.
[0011] Optionally, the alkali-soluble acrylic resin has a weight-average molecular weight of 13,000-17,000 and a molecular weight distribution of 1.8-2.4.
[0012] Optionally, the silane monomer includes 3-methacrylate oxypropyltriethoxysilane and / or 3-methacrylate oxypropyltrimethoxysilane.
[0013] Optionally, the photosensitive compound is a condensation product of a phenolic compound and 1,2-naphthoquinone diazide-5-sulfonyl chloride.
[0014] Optionally, the phenolic compound includes at least one of 4,4'-[1-[4-[1-[4-[4-hydroxyphenyl]-1-methylethyl]phenyl]ethylidene]bisphenol, 1,1,1-tris(p-hydroxyphenyl)ethane, and monophenolic compounds.
[0015] Optionally, the leveling agent includes polyether-modified polydimethylsiloxane and / or F-563.
[0016] Optionally, the organic solvent includes at least one of propylene glycol monomethyl ether acetate, diethylene glycol methyl ethyl ether, and propylene glycol monomethyl ether.
[0017] This application also provides an interlayer insulating film, the raw material of which includes the positive photosensitive resin composition.
[0018] This application also provides a method for preparing the interlayer insulating film, including: The positive photosensitive resin composition is disposed on a substrate to form a coating film; The coating is subjected to pre-baking, exposure and development processes in sequence to obtain a patterned coating. The patterned coating is subjected to heat curing to obtain the interlayer insulating film.
[0019] Optionally, the pre-baking process is carried out at a temperature of 80-110°C for a time of 100-160 seconds.
[0020] Optionally, the developing process takes 60-90 seconds.
[0021] Optionally, the developing solution used in the developing process includes an aqueous solution of tetramethylammonium hydroxide; the mass concentration of the aqueous solution of tetramethylammonium hydroxide is 0.4%-0.6%.
[0022] Optionally, the temperature for the heat curing treatment is 200-250℃, and the time is 30-60 minutes.
[0023] Optionally, in the exposure process, the light source is an i-line light source with a wavelength of 365nm.
[0024] Compared with the prior art, the beneficial effects of this application include: The copolymer composition of the resin simultaneously includes carboxyl-containing unsaturated monomers, phenolic hydroxyl-containing polymerizable monomers, alkyl (meth)acrylates, silane-containing unsaturated monomers, aromatic ring-containing unsaturated monomers, aliphatic cyclic backbone-containing unsaturated monomers, epoxy group-containing unsaturated monomers, tetrahydrofuran group-containing unsaturated monomers, and morpholine group-containing unsaturated monomers. Based on the synergistic effect of these monomer types, when the composition is cured, a cured film with excellent transmittance, etching resistance, and adhesion is ensured. Specifically, the aliphatic cyclic backbone-containing unsaturated monomers impart a rigid molecular chain structure to the cured film, which is beneficial for improving heat resistance and dry etching resistance; the aromatic ring-containing unsaturated monomers further enhance the thermal stability of the cured film; the silane-containing unsaturated monomers enhance the adhesion between the cured film and the substrate, thereby improving adhesion; and the tetrahydrofuran group-containing and morpholine group-containing unsaturated monomers help improve the optical properties of the cured film, increase light transmittance, and enhance resistance to organic solvents.
[0025] Furthermore, the carboxyl-containing unsaturated monomers in the resin of this application composition endow the resin with alkali solubility, ensuring good development performance of the composition in alkaline developer; at the same time, the synergistic effect between the monomers makes the resin dissolution rate in developer moderate, thus maintaining good pattern shape even when the development time exceeds the optimal range, effectively inhibiting pattern peeling. Therefore, the composition of this application has both high sensitivity and excellent development tolerance.
[0026] Furthermore, by controlling the specific ratio between the resin solution and the photosensitive compound, silane coupling agent, leveling agent and organic solvent, the composition of this application exhibits small viscosity changes and good storage stability during room temperature storage.
[0027] Compared with the prior art, the positive photosensitive resin composition provided in this application can simultaneously achieve high sensitivity, excellent development performance and storage stability. Furthermore, the cured film formed by it exhibits excellent performance in terms of light transmittance, solvent resistance, dry etching resistance and adhesion to the substrate, which can fully meet the high-performance requirements of interlayer insulating film materials for electronic components such as TFT liquid crystal display elements. Attached Figure Description
[0028] To more clearly illustrate the technical solutions of the embodiments of this application, the accompanying drawings used in the embodiments will be briefly described below. It should be understood that the following drawings only show some embodiments of this application and should not be regarded as a limitation on the scope of this application.
[0029] Figure 1 The morphology of CD-SEM after development; Figure 2 These are X-SEM images after heat curing. Detailed Implementation
[0030] As used in this article: "Prepared from" is synonymous with "comprising". The terms "comprising", "including", "having", "containing", or any other variations thereof as used herein are intended to cover non-exclusive inclusion. For example, a composition, step, method, article, or apparatus that includes the listed elements is not necessarily limited to those elements, but may include other elements not expressly listed or elements inherent to such composition, step, method, article, or apparatus.
[0031] The conjunction "composed of..." excludes any unspecified elements, steps, or components. If used in a claim, this phrase makes the claim closed, excluding materials other than those described, except for associated conventional impurities. When the phrase "composed of..." appears in a clause of the body of a claim rather than immediately following it, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.
[0032] When a quantity, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pair of any upper or preferred value with any lower or preferred value, regardless of whether the range is disclosed individually. For example, when the range “1-5” is disclosed, the described range should be interpreted as including ranges “1-4”, “1-3”, “1-2”, “1-2 and 4-5”, “1-3 and 5”, etc. When numerical ranges are described herein, unless otherwise stated, the range is intended to include its endpoints and all integers and fractions within that range.
[0033] In these embodiments, unless otherwise specified, the portions and percentages are all by weight.
[0034] "Parts by mass" refers to the basic unit of measurement that expresses the mass ratio of multiple components. One part can represent any unit mass, such as 1g or 2.689g. If we say that component A has "a" parts by mass and component B has "b" parts by mass, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it can mean that the mass of component A is aK and the mass of component B is bK (where K is any number representing a multiplier). It is important to understand that, unlike parts by mass, the sum of the mass parts of all components is not limited to 100 parts.
[0035] "And / or" is used to indicate that one or both of the described situations may occur, for example, A and / or B includes (A and B) and (A or B).
[0036] To better explain the technical solution provided in this application, the technical solution provided in this application will be described in general before the specific implementation.
[0037] In a first aspect, this application provides a positive photosensitive resin composition, wherein, by weight parts, the raw materials of the positive photosensitive resin composition include: 100 parts of alkali-soluble acrylic resin, 10-30 parts of photosensitive compound, 0.5-3 parts of silane coupling agent, 0.05-0.5 parts of leveling agent, and 30-80 parts of organic solvent.
[0038] Optionally, by mass parts: the amount of photosensitive compound can be 10 parts, 20 parts, 30 parts, or any value between 10 and 30 parts; the amount of silane coupling agent can be 0.5 parts, 1 part, 1.5 parts, 2 parts, 2.5 parts, 3 parts, or any value between 0.5 and 3 parts; the amount of leveling agent can be 0.05 parts, 0.1 parts, 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts, or any value between 0.05 and 0.5 parts; the amount of organic solvent can be 30 parts, 40 parts, 50 parts, 60 parts, 70 parts, 80 parts, or any value between 30 and 80 parts.
[0039] In an optional embodiment, the raw materials of the alkali-soluble acrylic resin, by weight parts, include: 10-153 parts methacrylic acid, 15-20 parts hydroquinone monomethacrylate, 4-22 parts methyl methacrylate, 4-8 parts silane monomer, 4-12 parts styrene, 5-10 parts dicyclopentyl methacrylate, 10-15 parts glycidyl methacrylate, 5-10 parts 3,4-epoxycyclohexylmethyl methacrylate, 15-20 parts tetrahydrofuran methacrylate, and 10-15 parts 4-acryloylmorpholine.
[0040] Optionally, by mass parts, the raw materials of the alkali-soluble acrylic resin include: methacrylic acid in amounts of 10, 11, 12, 13, 14, or 15 parts, or any value between 10 and 15 parts; hydroquinone monomethacrylate in amounts of 15, 16, 17, 18, 19, or 20 parts, or any value between 15 and 20 parts; methyl methacrylate in amounts of 4, 6, 8, 10, 12, 14, 16, 18, or 22 parts, or any value between 4 and 22 parts; silane monomer in amounts of 4, 5, 6, 7, or 8 parts, or any value between 4 and 8 parts; and styrene in amounts of 4, 5, 6, 7, 8, 9, 10, 11, or 12 parts, or any value between 4 and 22 parts. The amount of dicyclopentyl methacrylate can be 5, 6, 7, 8, 9, or 10 parts, or any value between 5 and 10 parts; the amount of glycidyl methacrylate can be 10, 11, 12, 13, 14, or 15 parts, or any value between 10 and 15 parts; the amount of 3,4-epoxycyclohexylmethyl methacrylate can be 5, 6, 7, 8, 9, or 10 parts, or any value between 5 and 10 parts; the amount of tetrahydrofuran methacrylate can be 15, 16, 17, 18, 19, or 20 parts, or any value between 15 and 20 parts; the amount of 4-acryloylmorpholine can be 10, 11, 12, 13, 14, or 15 parts, or any value between 10 and 15 parts.
[0041] In one optional embodiment, the alkali-soluble acrylic resin is a homogeneous solution.
[0042] The solid content of the homogeneous solution is 30-40 wt%; The solvent for the homogeneous solution includes diethylene glycol methyl ethyl ether.
[0043] Optionally, the solid content in the homogeneous solution can be 30 wt%, 35 wt%, 40 wt%, or any value between 30 and 40 wt%.
[0044] In one optional embodiment, the alkali-soluble acrylic resin has a weight-average molecular weight of 13,000-17,000 and a molecular weight distribution of 1.8-2.4.
[0045] Optionally, the weight-average molecular weight of the alkali-soluble acrylic resin can be 13,000, 14,000, 15,000, 16,000, 17,000, or any value between 13,000 and 17,000; the molecular weight distribution can be 1.8, 2.0, 2.1, 2.2, 2.3, 2.4, or any value between 1.8 and 2.4.
[0046] In an optional embodiment, the silane monomer comprises 3-methacrylate oxypropyltriethoxysilane and / or 3-methacrylate oxypropyltrimethoxysilane.
[0047] In an optional embodiment, the photosensitive compound is a condensation of a phenolic compound and 1,2-naphthoquinone diazide-5-sulfonyl chloride.
[0048] In an optional embodiment, the phenolic compound includes at least one of 4,4'-[1-[4-[1-[4-[4-hydroxyphenyl]-1-methylethyl]phenyl]ethylidene]bisphenol, 1,1,1-tris(p-hydroxyphenyl)ethane, and monophenolic compounds.
[0049] In an optional embodiment, the leveling agent comprises polyether-modified polydimethylsiloxane and / or F-563.
[0050] In an optional embodiment, the organic solvent includes at least one of propylene glycol monomethyl ether acetate, diethylene glycol methyl ethyl ether, and propylene glycol monomethyl ether.
[0051] Secondly, this application also provides an interlayer insulating film, the raw material of which includes the positive photosensitive resin composition.
[0052] Thirdly, this application also provides a method for preparing the interlayer insulating film, comprising: The positive photosensitive resin composition is disposed on a substrate to form a coating film; The coating is subjected to pre-baking, exposure and development processes in sequence to obtain a patterned coating. The patterned coating is subjected to heat curing to obtain the interlayer insulating film.
[0053] In one optional embodiment, the pre-baking process is carried out at a temperature of 80-110°C for a time of 100-160 seconds.
[0054] Optionally, the pre-baking temperature can be 80℃, 90℃, 100℃, 110℃, 120℃, or any value between 80℃ and 120℃; the pre-baking time can be 100s, 120s, 130s, 140s, 150s, 160s, or any value between 110s and 160s.
[0055] In one optional implementation, the developing process takes 60-90 seconds.
[0056] Optionally, the development time can be 60s, 70s, 80s, 90s, or any value between 60 and 90s.
[0057] In an optional embodiment, the developing solution used in the developing process comprises an aqueous solution of tetramethylammonium hydroxide; the mass concentration of the aqueous solution of tetramethylammonium hydroxide is 0.4%-0.6%.
[0058] Optionally, the mass concentration of the tetramethylammonium hydroxide aqueous solution can be 0.4%, 0.5%, 0.6%, or any value between 0.4% and 0.6%.
[0059] In one optional embodiment, the temperature of the heat curing treatment is 200-250°C, and the time is 30-60 minutes.
[0060] Optionally, the temperature for heat curing can be 200℃, 210℃, 220℃, 230℃, 240℃, 250℃, or any value between 200℃ and 250℃; the time for heat curing can be 30min, 40min, 50min, 60min, or any value between 30min and 60min.
[0061] In one optional implementation, the light source in the exposure process is an i-line light source with a wavelength of 365nm.
[0062] The implementation schemes of this application will be described in detail below with reference to specific embodiments. However, those skilled in the art will understand that the following embodiments are only for illustrating this application and should not be regarded as limiting the scope of this application. Unless otherwise specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments used without specified manufacturers are all conventional products that can be purchased commercially.
[0063] Example 1 This embodiment provides a positive photosensitive resin composition: The raw materials, by mass parts, include: 100 parts of alkali-soluble acrylic resin, 20 parts of photosensitive compound, 1 part of silane coupling agent, 0.15 parts of leveling agent, and 50 parts of organic solvent.
[0064] The alkali-soluble acrylic resin is a homogeneous solution with a solid content of 34.9%, and the solvent is diethylene glycol methyl ethyl ether. The raw materials for this resin, by mass parts, include: 13 parts methacrylic acid, 18 parts hydroquinone monomethacrylate, 8 parts methyl methacrylate, 4 parts 3-methacrylateoxypropyltriethoxysilane, 4 parts styrene, 6 parts dicyclopentyl methacrylate, 12 parts glycidyl methacrylate, 6 parts 3,4-epoxycyclohexylmethyl methacrylate, 18 parts tetrahydrofuran methacrylate, 11 parts 4-acryloylmorpholine, 7 parts azobisisoheptanenitrile, and 200 parts diethylene glycol methyl ethyl ether.
[0065] The above raw materials were copolymerized to obtain an alkali-soluble acrylic resin: 13 parts by mass of methacrylic acid, 18 parts by mass of hydroquinone monomethacrylate, 8 parts by mass of methyl methacrylate, 4 parts by mass of 3-methacrylateoxypropyltriethoxysilane, 4 parts by mass of styrene, 6 parts by mass of dicyclopentyl methacrylate, 12 parts by mass of glycidyl methacrylate, 6 parts by mass of 3,4-epoxycyclohexylmethyl methacrylate, 18 parts by mass of tetrahydrofuranyl methacrylate, 11 parts by mass of 4-acryloylmorpholine, and a certain amount of diethylene glycol methyl ether solvent were added to a 500 mL four-necked flask. 7 parts by mass of azobisisobutyronitrile was added to the flask as an initiator for the polymerization reaction, and the reaction was carried out at 85°C for 6 hours under a nitrogen atmosphere. After the reaction was completed, the reaction solution was cooled to obtain an acrylic resin solution with diethylene glycol methyl ether as the solvent. Its weight-average molecular weight was 15,000, and its molecular weight distribution was 2.1.
[0066] The photosensitive compound was a condensate of 4,4'-[1-[4-[1-[4-hydroxyphenyl]-1-methylethyl]phenyl]ethylidene]bisphenol (1.0 mol) and 1,2-naphthoquinone diazide-5-sulfonyl chloride (3.0 mol) (purchased from Changzhou Qiangli Electronic New Materials Co., Ltd.). The silane coupling agent was γ-glycidyl etheroxypropyltrimethoxysilane, the leveling agent was a polysiloxane leveling agent, and the organic solvent was propylene glycol monomethyl ether acetate.
[0067] The above components are mixed to obtain a homogeneous solution, which is then filtered using a 0.2 μm polytetrafluoroethylene filter to obtain a positive photosensitive resin composition solution.
[0068] This embodiment also provides an interlayer insulating film, the specific steps of which are as follows: The above-mentioned positive photosensitive resin composition solution was spin-coated onto a glass substrate and pre-baked on a hot plate at 95°C for 130 seconds to form a coating with a thickness of 4.6 μm. Exposure was performed using an i-line exposure machine (Nikon, i9, wavelength 365 nm) through a predetermined mask. Then, it was developed with a 0.5% tetramethylammonium hydroxide aqueous solution at 23°C for 70 seconds, followed by rinsing with ultrapure water for 1 minute. The developed patterned coating was cured in a hot plate at 230°C for 40 minutes to obtain an interlayer insulating film. The CD-SEM morphology after development is shown below. Figure 1 As shown, the X-SEM image after heat curing is as follows: Figure 2 As shown.
[0069] Example 2 This embodiment provides a positive photosensitive resin composition, which differs from Example 1 only in that: the alkali-soluble acrylic resin is replaced by a resin with the following composition in Example 1: 13 parts by weight of methacrylic acid, 18 parts by weight of hydroquinone monomethacrylate, 6 parts by weight of methyl methacrylate, 6 parts by weight of 3-methacrylic acid oxypropyltriethoxysilane, 4 parts by weight of styrene, 6 parts by weight of dicyclopentyl methacrylate, 12 parts by weight of glycidyl methacrylate, 6 parts by weight of 3,4-epoxycyclohexylmethyl methacrylate, 18 parts by weight of tetrahydrofuran methacrylate, and 11 parts by weight of 4-acryloylmorpholine, which are copolymerized to obtain an alkali-soluble acrylic resin solution (solid content 34.9%, weight average molecular weight 15000, molecular weight distribution 2.1); a fluorinated leveling agent is used instead of a polysiloxane leveling agent; and diethylene glycol methyl ethyl ether is used instead of propylene glycol monomethyl ether acetate as the organic solvent.
[0070] Example 3 This embodiment provides a positive photosensitive resin composition, which differs from Example 1 only in that: the alkali-soluble acrylic resin is replaced by a resin with the following composition in Example 1: 13 parts by weight of methacrylic acid, 18 parts by weight of hydroquinone monomethacrylate, 4 parts by weight of methyl methacrylate, 8 parts by weight of 3-methacrylic acid oxypropyltriethoxysilane, 4 parts by weight of styrene, 6 parts by weight of dicyclopentyl methacrylate, 12 parts by weight of glycidyl methacrylate, 6 parts by weight of 3,4-epoxycyclohexylmethyl methacrylate, 18 parts by weight of tetrahydrofuran methacrylate, and 11 parts by weight of 4-acryloylmorpholine, which are copolymerized to obtain an alkali-soluble acrylic resin solution (solid content 34.9%, weight average molecular weight 15000, molecular weight distribution 2.1); the organic solvent is replaced by propylene glycol monomethyl ether instead of propylene glycol monomethyl ether acetate.
[0071] Example 4 This embodiment provides a positive photosensitive resin composition, differing from Example 1 only in that the alkali-soluble acrylic resin is replaced with the following composition in Example 1: 13 parts by weight of methacrylic acid, 18 parts by weight of hydroquinone monomethacrylate, 8 parts by weight of methyl methacrylate, 4 parts by weight of 3-methacrylic acid oxypropyltrimethoxysilane, 4 parts by weight of styrene, 6 parts by weight of dicyclopentyl methacrylate, 12 parts by weight of glycidyl methacrylate, 6 parts by weight of 3,4-epoxycyclohexylmethyl methacrylate, 18 parts by weight of tetrahydrofuran methacrylate, and 11 parts by weight of 4-acryloylmorpholine, yielding an alkali-soluble acrylic resin solution (solid content 34.9%) through copolymerization. (%), weight average molecular weight 15000, molecular weight distribution 2.1); the photosensitive compound was replaced by a condensate of 1,1,1-tris(p-hydroxyphenyl)ethane (1.0 mol) and 1,2-naphthoquinone diazide-5-sulfonyl chloride (3.0 mol); the leveling agent was replaced by a fluorinated leveling agent instead of a polysiloxane leveling agent.
[0072] Example 5 This embodiment provides a positive photosensitive resin composition, differing from Example 1 only in that the alkali-soluble acrylic resin is replaced with the following composition in Example 1: 13 parts by weight of methacrylic acid, 18 parts by weight of hydroquinone monomethacrylate, 6 parts by weight of methyl methacrylate, 6 parts by weight of 3-methacrylic acid oxypropyltrimethoxysilane, 4 parts by weight of styrene, 6 parts by weight of dicyclopentyl methacrylate, 12 parts by weight of glycidyl methacrylate, 6 parts by weight of 3,4-epoxycyclohexylmethyl methacrylate, 18 parts by weight of tetrahydrofuran methacrylate, and 11 parts by weight of 4-acryloylmorpholine, yielding an alkali-soluble acrylic resin solution (solid content 34.9%) through copolymerization. (%), weight average molecular weight 15000, molecular weight distribution 2.1); the photosensitive compound was replaced by a condensate of 1,1,1-tris(p-hydroxyphenyl)ethane (1.0 mol) and 1,2-naphthoquinone diazide-5-sulfonyl chloride (3.0 mol); the organic solvent was replaced by diethylene glycol methyl ether instead of propylene glycol monomethyl ether acetate.
[0073] Example 5 This embodiment provides a positive photosensitive resin composition, differing from Example 1 only in that the alkali-soluble acrylic resin is replaced with the following composition in Example 1: 13 parts by weight of methacrylic acid, 18 parts by weight of hydroquinone monomethacrylate, 6 parts by weight of methyl methacrylate, 6 parts by weight of 3-methacrylic acid oxypropyltrimethoxysilane, 4 parts by weight of styrene, 6 parts by weight of dicyclopentyl methacrylate, 12 parts by weight of glycidyl methacrylate, 6 parts by weight of 3,4-epoxycyclohexylmethyl methacrylate, 18 parts by weight of tetrahydrofuran methacrylate, and 11 parts by weight of 4-acryloylmorpholine, yielding an alkali-soluble acrylic resin solution (solid content 34.9%) through copolymerization. (%), weight average molecular weight 15000, molecular weight distribution 2.1); the photosensitive compound was replaced by a condensate of 1,1,1-tris(p-hydroxyphenyl)ethane (1.0 mol) and 1,2-naphthoquinone diazide-5-sulfonyl chloride (3.0 mol); the organic solvent was replaced by diethylene glycol methyl ether instead of propylene glycol monomethyl ether acetate.
[0074] Example 6 This embodiment provides a positive photosensitive resin composition, differing from Example 1 only in that the alkali-soluble acrylic resin is replaced with the following composition in Example 1: 13 parts by weight of methacrylic acid, 18 parts by weight of hydroquinone monomethacrylate, 4 parts by weight of methyl methacrylate, 8 parts by weight of 3-methacrylateoxypropyltrimethoxysilane, 4 parts by weight of styrene, 6 parts by weight of dicyclopentyl methacrylate, 12 parts by weight of glycidyl methacrylate, 6 parts by weight of 3,4-epoxycyclohexylmethyl methacrylate, 18 parts by weight of tetrahydrofuran methacrylate, and 11 parts by weight of 4-acryloylmorpholine, yielding an alkali-soluble acrylic resin solution (solid content 34.9%) through copolymerization. (%), weight average molecular weight 15000, molecular weight distribution 2.1); the photosensitive compound was replaced by a condensate of 1,1,1-tris(p-hydroxyphenyl)ethane (1.0 mol) and 1,2-naphthoquinone diazide-5-sulfonyl chloride (3.0 mol); the organic solvent was replaced by propylene glycol monomethyl ether instead of propylene glycol monomethyl ether acetate.
[0075] Comparative Example 1 This comparative example provides a positive photosensitive resin composition, which differs from Example 1 only in that the alkali-soluble acrylic resin is replaced with a resin of the following composition: 13 parts by weight of methacrylic acid, 18 parts by weight of hydroquinone monomethacrylate, 22 parts by weight of methyl methacrylate, 12 parts by weight of styrene, 6 parts by weight of dicyclopentyl methacrylate, 12 parts by weight of glycidyl methacrylate, 6 parts by weight of 3,4-epoxycyclohexylmethyl methacrylate, and 11 parts by weight of 4-acryloylmorpholine. The resulting alkali-soluble acrylic resin solution (solid content 34.9%, weight average molecular weight 15000, molecular weight distribution 2.1) is obtained by copolymerization. This resin does not contain 3-methacrylateoxypropyltriethoxysilane, 3-methacrylateoxypropyltrimethoxysilane, or tetrahydrofuran methacrylate.
[0076] Comparative Example 2 This comparative example provides a positive photosensitive resin composition, which differs from Example 1 only in that: the alkali-soluble acrylic resin used is the resin described in Comparative Example 1 instead of the resin in Example 1, and the amount of the resin used is 90 parts by weight (100 parts by weight in Example 1).
[0077] Comparative Example 3 This comparative example provides a positive photosensitive resin composition, which differs from Example 1 only in that: the alkali-soluble acrylic resin is replaced by the resin described in Comparative Example 1, and the amount of the resin used is 110 parts by weight (100 parts by weight in Example 1).
[0078] Comparative Example 4 This comparative example provides a positive photosensitive resin composition, which differs from Example 1 only in that the photosensitive compound is replaced by a 2-diazo-1-naphthol-5-sulfonyl chloride monophenol condensate instead of the photosensitive compound in Example 1.
[0079] The compositions of the resins synthesized by the methods provided in Examples 1-6 and Comparative Example 1 are shown in Table 1: Table 1 Resin composition in the examples and comparative examples.
[0080] in: MA: Methacrylic acid; PQMA: p-diphenyl monomethacrylate; MMA: Methyl methacrylate; MPTES: 3-Methylacrylate oxypropyltriethoxysilane; MPTMS: 3-Methylacrylate oxypropyltrimethoxysilane; St: Styrene; DCPMA: Dicyclopentyl methacrylate; GMA: Glycidyl methacrylate; TTA-15: 3,4-Epoxycyclohexylmethyl methacrylate; THFMA: Tetrahydrofuran methacrylate; ACMO: 4-Acryloylmorpholine; ABVN: Azobisisoheptanenitrile; EDM: Diethylene glycol methyl ethyl ether.
[0081] The raw material compositions of Examples 1-6 and Comparative Examples 1-4 are shown in Table 2: Table 2. Raw material composition of the examples and comparative examples
[0082] in: Component (B): B-1: A condensation product of 4,4'-[1-[4-[1-[4-hydroxyphenyl]-1-methylethyl]phenyl]ethylidene]bisphenol (1.0 mol) and 1,2-naphthoquinone diazide-5-sulfonyl chloride (3.0 mol); B-2: A condensation product of 1,1,1-tris(p-hydroxyphenyl)ethane (1.0 mol) and 1,2-naphthoquinone diazide-5-sulfonyl chloride (3.0 mol); B-3:2-diazo-1-naphthol-5-sulfonyl chloride monophenol condensate.
[0083] Component (C): C-1: γ-glycidoxypropyltrimethoxysilane; Component (D): D-1: Polyether-modified polydimethylsiloxane; D-2: F-563.
[0084] Component (E): E-1: Propylene glycol monomethyl ether acetate; E-2: Diethylene glycol methyl ethyl ether; E-3: Propylene glycol monomethyl ether.
[0085] The performance of the positive photosensitive resin compositions and interlayer insulating films prepared in each embodiment and comparative example was evaluated using the following test methods: Sensitivity Evaluation: The positive-type photosensitive resin composition solution was spin-coated onto a glass substrate and then pre-baked at 95°C for 130 s to form a 4.6 μm thick film. Exposure was performed using an i-line exposure machine (Nikon, i9) through a predetermined mask, followed by development with a 0.5% tetramethylammonium hydroxide aqueous solution at 23°C for 70 s, and then rinsing with ultrapure water for 1 minute. The minimum exposure required to obtain 4 μm apertures was defined as the sensitivity. The sensitivity evaluation results are shown in Table 3.
[0086] Transmittance: Each photoresist composition solution was spin-coated onto a glass substrate treated with hexamethyldisilazane vapor using a spin coater, then baked on a hot plate at 95°C for 130 seconds, followed by general exposure (IUV=400mJ), and then baked on a hot plate at 230°C for 40 minutes to obtain a 4.0μm cured film. The transmittance at wavelengths of 380-780nm was measured using a Shimadzu UV-1900i dual-beam UV-Vis spectrophotometer. The transmittance at 400nm was used as the final criterion; the closer the result was to 100%, the better the result; a result below 95% was considered unacceptable. The transmittance evaluation results are shown in Table 3.
[0087] Adhesion evaluation: Using a cutting machine, the cured film obtained by baking at 230℃ for 40 min was longitudinally and transversely cut at 1 mm intervals. A Scotch tape peel test was then performed. The adhesion between the cured film and the substrate was evaluated based on the area of cured film transferred to the back of the tape. When this area was less than 1%, the adhesion was rated "A"; when the area was greater than or equal to 1% but less than 5%, the adhesion was rated "B"; and when the area was greater than or equal to 5%, the adhesion was rated "C". The results of the adhesion evaluation are shown in Table 3.
[0088] Storage stability evaluation: The viscosity of the photoresist formulation solution at 23°C was measured using a viscometer. Additionally, the viscosity of each composition was measured after one month of storage in a 23°C constant temperature bath. Comparing the viscosity changes, a composition was rated "A" if the viscosity increase rate was less than 5%, and "B" if the viscosity increase rate was greater than or equal to 5%. The results of the storage stability evaluation are shown in Table 3.
[0089] Solvent resistance evaluation: Similar to the transmittance evaluation, a cured film was formed on a silicon substrate. A cross-cut tester was used to make 1mm intervals on the film, and its morphology was observed under a microscope. The cured film was then immersed in N-methylpyrrolidone (NMP) at 23°C for 5 minutes. Afterward, the film was observed under a microscope for any peeling. If the morphology remained consistent before and after immersion in NMP solvent, and no cured film peeling occurred, the solvent resistance was good, and the evaluation was "A"; if the cured film peeled off, the solvent resistance was poor, and the evaluation was "B". The evaluation results are shown in Table 3.
[0090] Etching resistance evaluation: Similar to the solvent resistance evaluation above, a cured film was formed on a silicon substrate. Dry etching was performed using a CDE-80N dry etching apparatus under the following conditions: CF4 10 ml / min, O2 12 ml / min, output 120 W, pressure 15 mtorr, and etching time 400 seconds. The film thickness was measured before and after the treatment. A film thickness reduction of less than 1.00 μm was considered to indicate good etching resistance. The evaluation results are shown in Table 3.
[0091] Table 3 Evaluation results of the interlayer insulating films provided in the examples and comparative examples
[0092] According to Table 3: Sensitivity: The sensitivity of Examples 1-6 is all between 28-35 mJ / cm. 2 The sensitivity of the samples was between 45 and 50 mJ / cm², while that of the samples 1-4 was between 45 and 50 mJ / cm². 2 This indicates that by introducing tetrahydrofuran methacrylate and silane-containing unsaturated monomers into the copolymer composition of an alkali-soluble acrylic resin, and combining a condensate of a phenolic compound with 1,2-naphthoquinone diazide-5-sulfonyl chloride as a photosensitizing compound, the sensitivity of the composition can be significantly improved. Comparative Examples 1-3, due to the use of resins without tetrahydrofuran methacrylate and silane-containing unsaturated monomers, exhibited significantly lower sensitivity than the examples. Although Comparative Example 4 used the same resin as Example 1, its sensitivity also decreased significantly due to the replacement of the photosensitizing compound with a 2-diazo-1-naphthol-5-sulfonyl chloride monophenol condensate, indicating that the polyphenolic diazinonaphthoquinone compound with a specific structure plays a crucial role in achieving high sensitivity.
[0093] Transmittance: The transmittance of Examples 1-6 at a wavelength of 400nm was between 96% and 97%, all higher than the 95% threshold. Comparative Example 2 had a transmittance of 93.5%, lower than the 95% threshold, and therefore did not meet the standard. While the transmittance of the other comparative examples was higher than 95%, they did not offer any advantage over the examples. It is worth noting that although Comparative Examples 1 and 4 had transmittance as high as 99%, they exhibited significant deficiencies in other properties (storage stability, solvent resistance, sensitivity, etc.), indicating that simply pursuing high transmittance at the expense of other properties is meaningless. The embodiments of this application achieve a balance between high transmittance and other performance characteristics.
[0094] Adhesion: The adhesion of Examples 1-6 was rated "A", indicating that the cured film formed by the composition of this application has good adhesion to the substrate. This is because the silane-containing unsaturated monomers (3-methacrylate oxypropyltriethoxysilane or 3-methacrylate oxypropyltrimethoxysilane) in the resin copolymer composition can form chemical bonds with the hydroxyl groups on the substrate surface during curing, thereby significantly enhancing the adhesion. Comparative Examples 1-3, because they used resins without silane monomers, still achieved an adhesion rating of "A", but this was at the expense of other properties and has no practical application value. The adhesion of Comparative Example 2 was rated "B", further illustrating that when the amount of resin (A) deviates from the preferred range, the adhesion performance is also affected.
[0095] Storage stability: The storage stability of Examples 1-6 was rated as "A", meaning the viscosity increase rate after one month at room temperature was less than 5%. The storage stability of Comparative Examples 1-4 was rated as "B", meaning the viscosity increase rate was greater than or equal to 5%. This indicates that the specific resin composition and synergistic effect of the components in this application enable the composition to maintain good chemical stability during storage, and it is less prone to side reactions such as crosslinking or decomposition that lead to increased viscosity. In the comparative examples, whether it was the resin lacking the key monomer used in Comparative Examples 1-3 or the monophenol condensate used in Comparative Example 4, both exhibited insufficient storage stability.
[0096] Solvent resistance: The solvent resistance of Examples 1-6 was rated as "A", meaning no film peeling occurred after immersion in N-methylpyrrolidone. This indicates that the cured film formed by the compositions of this application has a high crosslinking density and chemical stability, and can withstand the erosion of organic solvents. The solvent resistance of Comparative Examples 2 and 4 was rated as "B", indicating that film peeling occurred. In Comparative Example 2, the crosslinking density of the cured film was insufficient due to the low amount of resin (A) (90 parts by weight); in Comparative Example 4, the crosslinking structure formed after curing was not dense enough due to the use of 2-diazo-1-naphthol-5-sulfonyl chloride monophenol condensate instead of polyphenol condensate, resulting in decreased solvent resistance.
[0097] Etching Resistance: The film thickness reduction in Examples 1-6 was between 0.63-0.95 μm, all less than 1.00 μm, indicating that the cured film formed by the composition of this application has excellent dry etching resistance. The film thickness reduction in Comparative Examples 1-3 was between 1.52-1.55 μm, all greater than 1.00 μm, indicating insufficient etching resistance. This is because resin a-1 does not contain unsaturated monomers with silane groups, resulting in a lack of silicon in the cured film. The introduction of silicon can significantly improve the resistance of the cured film to plasma etching. Although the film thickness reduction in Comparative Example 4 was 0.90 μm, less than 1.00 μm, it still failed to meet the overall performance requirements due to its deficiencies in sensitivity, storage stability, and solvent resistance.
[0098] In summary, Examples 1-6 of this application exhibit excellent performance in terms of sensitivity, transmittance, adhesion, storage stability, solvent resistance, and etching resistance, fully meeting the high-performance requirements of interlayer insulating film materials for electronic components such as TFT-type liquid crystal display elements. In contrast, each comparative example has at least one performance defect, failing to achieve a balanced balance of various performance characteristics. This indicates that the positive photosensitive resin composition of this application, through the synergistic combination of specific monomers in the resin and the synergistic effect between the resin, photosensitive compound (B), silane coupling agent, leveling agent, and organic solvent, can maintain high sensitivity while also achieving excellent development performance, storage stability, optical performance, solvent resistance, and etching resistance, demonstrating promising prospects for industrial applications.
[0099] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application, and are not intended to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of this application.
[0100] Furthermore, those skilled in the art will understand that although some embodiments herein include certain features included in other embodiments but not others, combinations of features from different embodiments are intended to be within the scope of this application and form different embodiments. For example, in the foregoing claims, any of the claimed embodiments can be used in any combination. The information disclosed in this background section is intended only to enhance the understanding of the general background of this application and should not be construed as an admission or in any way implying that such information constitutes prior art known to those skilled in the art.
Claims
1. A positive photosensitive resin composition, characterized in that, The raw materials of the positive photosensitive resin composition, by weight, include: 100 parts of alkali-soluble acrylic resin, 10-30 parts of photosensitive compound, 0.5-3 parts of silane coupling agent, 0.05-0.5 parts of leveling agent, and 30-80 parts of organic solvent.
2. The positive photosensitive resin composition according to claim 1, characterized in that, The raw materials of the alkali-soluble acrylic resin, by weight, include: 10-15 parts methacrylic acid, 15-20 parts hydroquinone monomethacrylate, 4-22 parts methyl methacrylate, 4-8 parts silane monomer, 4-12 parts styrene, 5-10 parts dicyclopentyl methacrylate, 10-15 parts glycidyl methacrylate, 5-10 parts 3,4-epoxycyclohexylmethyl methacrylate, 15-20 parts tetrahydrofuran methacrylate, and 10-15 parts 4-acryloylmorpholine.
3. The positive photosensitive resin composition according to claim 2, characterized in that, At least one of the following conditions must be met: a. The alkali-soluble acrylic resin is a homogeneous solution; The solid content of the homogeneous solution is 30-40 wt%; The solvent for the homogeneous solution includes diethylene glycol methyl ethyl ether; b. The weight-average molecular weight of the alkali-soluble acrylic resin is 13,000-17,000, and the molecular weight distribution is 1.8-2.
4. c. The silane monomers include 3-methacrylate oxypropyltriethoxysilane and / or 3-methacrylate oxypropyltrimethoxysilane.
4. The positive photosensitive resin composition according to claim 1, characterized in that, The photosensitive compound is a condensation product of a phenolic compound and 1,2-naphthoquinone diazide-5-sulfonyl chloride.
5. The positive photosensitive resin composition according to claim 4, characterized in that, The phenolic compounds include at least one of 4,4'-[1-[4-[1-[4-[4-hydroxyphenyl]-1-methylethyl]phenyl]ethylidene]bisphenol, 1,1,1-tris(p-hydroxyphenyl)ethane, and monophenolic compounds.
6. The positive photosensitive resin composition according to claim 1, characterized in that, The leveling agent includes polyether-modified polydimethylsiloxane and / or F-563.
7. The positive photosensitive resin composition according to any one of claims 1-6, characterized in that, The organic solvent includes at least one of propylene glycol monomethyl ether acetate, diethylene glycol methyl ethyl ether, and propylene glycol monomethyl ether.
8. An interlayer insulating film, characterized in that, The raw materials include the positive photosensitive resin composition according to any one of claims 1-7.
9. A method for preparing the interlayer insulating film according to claim 8, characterized in that, include: The positive photosensitive resin composition is disposed on a substrate to form a coating film; The coating is subjected to pre-baking, exposure and development processes in sequence to obtain a patterned coating. The patterned coating is subjected to heat curing to obtain the interlayer insulating film.
10. The method for preparing an interlayer insulating film according to claim 9, characterized in that, At least one of the following conditions must be met: A. The pre-baking treatment is performed at a temperature of 80-110℃ for a time of 100-160 seconds; B. The development process takes 60-90 seconds; C. The developing solution used in the developing process comprises an aqueous solution of tetramethylammonium hydroxide; the mass concentration of the aqueous solution of tetramethylammonium hydroxide is 0.4%-0.6%; D. The temperature for the heat curing treatment is 200-250℃, and the time is 30-60 minutes; E. In the exposure process, the light source is an i-line light source with a wavelength of 365nm.